THE USE OF LANGUAGE ASPECT IN THE DISCOURSE OF POLITICAL ADVERTISING IN PADANG - Alex Darmawan (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
Political advertisement has its own phenomenon since it is presented at specific time. It commonly shows up at any specific time during the legislative (lawmakers) and executive (president, governor, regent, mayor) election. This research aims to describe the elements, the structure, and the use of linguistic aspects in political advertising in Padang. This research involves three stages; data provision, data analysis, and presentation of analysis results. At the first stage, data was collected by finding out clippings concerning political advertising in 2009. They were further photographed and recorded. The analysis applies contextual method based on theories of socio-pragmatics. The analysis results are presented in descriptive manners. The structures of political advertisements in Padang have been shaped by two components, which are categorized into main and explanatory components. Besides, the use of linguistic aspects of the political advertisement in the city comprises capital letters, repetition, abbreviations, acronyms, code switching, code mixing, rhymes, couplets, metaphors, and antithesis.